The Effect of Academic Stress on Sleep Quality Mediated by School Burnout Among High School Students - Kurniawan, Leonardo Johanes; Wardani, Ria (Universitas Muhammadiyah Surakarta, 2023)
Abstract. Academic stress is a factor that affects sleep quality. In this study, the variable that mediates the effect of academic stress to sleep quality is school burnout which is studied in the context of online learning. The research was conducted using quantitative research methods to 307 high school students in Bandung through snowball sampling. Each participant filled out the Student-Life Stress Inventory, the Secondary School Burnout Scale, and the Pittsburgh Sleep Quality Index. The data were analyzed using the Structural Equation Modeling (SEM-PLS) technique. Based on the results of the mediation model test, the VAF number was 0.17 (17% 20%) which means that school burnout does not have a mediating effect on the effect of academic stress to sleep quality. Academic stress is more accurately seen as a direct effect. Another finding is that conflict indicator is less to represent academic stress, as well as burnout from family and burnout from studying less predict the school burnout. However, daytime dysfunction is the most representative component of sleep quality. Based on the outer loading, there are factors of academic stress, school burnout, and sleep quality that less to represent these variables. The findings reflect cultural bias. That is why this study suggests future researchers to use measuring instrument which not have risk of cultural bias.Keywords: academic stress; high school students; school burnout; sleep quality.